Measurement of distance and angle between the arytenoids in eastern Indian population and their applied importance - Shirshendu Ganguly (Al Ameen Journal of Medical Sciences, 2015)
Objectives: The inter-arytenoid distance and inter-arytenoid angle have predictive significance for the development of iatrogenic subglottic stenosis (SGS) or arytenoid subluxation/ dislocation (AS/AD). Method: Present work was conducted over a period of one year in the Dept. of Forensic & State Medicine, in a state-run hospital in Kolkata. The inter-arytenoid distance, the inter-arytenoid angle and the stature of 150 fresh cadaveric samples of both the sexes, between 18-80 years of age were measured and compared for their predictive use. Result: The inter-arytenoid distance obtained in males ranges between 11.16 & 16.68mms, that in females ranges between 8.38 & 13.88mms. This distance has a higher correlation with the stature of the individual in males than in females. The females tend to have a more acute inter-arytenoid angle, between 36 & 46 degrees, while the men have a wider angulation, between the 38 & 48 degrees. Conclusion: The present study states that the inter-arytenoid distance is significantly less in females than in males, as does the angle. The narrower and more acute angled posterior part of the subglottis proposes a gender bias for iatrogenic injuries towards the females in absence of use of properly calibrated endotracheal tubes. Further, statistically significant correlation between the stature and the inter-arytenoid distance can be used to choose the proper sized endotracheal tube especially in males. Hence the results of this study can be used to prevent or reduce the complications of the post-intubational injuries like subglottic stenosis and subluxation or dislocation of arytenoids in the different genders amongst the Eastern Indian subjects.